Strategies employed by external facilitators to support and sustain communities of practice among teachers. - Barrios-Espinosa, María Elvira; Sanchidrián-Blanco, María del Carmen; Torres-Sánchez, María Mónica; Gallego-García, María del Mar; Arcos de Torres, Rosa María (My University, 2024)
This paper explores the strategies employed by facilitators in supporting communities of practice among in-service teachers in Andalusia, Spain. As collaborative professional development approaches for teachers gain popularity, research highlights the crucial role of facilitation in the effectiveness and sustainability of these communities. Facilitators, often former experienced teachers, work as trainers in official institutions responsible for teachers' professional development. The study conducted five focus groups with facilitators, identifying strategies that align with those found in previous research on university teachers' Professional Learning Communities (PLCs). The strategies identified are categorized into five groups: Group Work Strategies: Enhance collaboration and group interactions, creating a conducive environment for teacher learning. Knowledge-Building Strategies: Advance teachers' pedagogical knowledge and improve their practice. Reflection Strategies: Encourage both individual and collective reflection among teachers. Communication-Facilitating Strategies: Optimize communication effectiveness within the group, ensuring active participation of all members. Bureaucracy-Facilitating Strategies: Help manage the administrative aspects of formal collaborative development initiatives. These strategies are key to fostering effective professional development and ensuring active engagement and sustained growth within teacher communities.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Professional learning communities; Facilitation